Introduction to criminal justice - Robert M. Bohm (McGraw-Hill, 2007)
This accessible yet comprehensive introduction to criminal justice in the United States has been dramatically updated and revised to include coverage of criminal justice's new, expanded role in the war on terrorism as well as to incorporate other recent developments, cases, and research in the field. Bohm and Haley have more than 50 years of combined experience in teaching introduction to criminal justice as well as working in criminal justice -- Bohm as a correctional officer and Haley as a police officer. An optional package combines the text with Reel Justice Interactive Movie CD-ROM